1999
DOI: 10.1177/014860719902300502
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of the Small Intestinal Epithelium

Abstract: The primary factors in feeding premature infants are dependent on the development and maturation of digestion and absorption. The maturation of digestive and absorptive functions of carbohydrates, proteins, fats, minerals, and vitamins in the young premature infant were determined in relation to availability of hydrolytic enzymes, such as lipases, proteases, amylases, glucosidases, and lactase. The feeding is dependent on the ability of the premature infant to secrete salivary enzymes, gastric acid, pepsin, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 15 publications
1
79
0
1
Order By: Relevance
“…A likely explanation for this absence of full differentiation could reside in the selection during the primocultures of lowly differentiated stem cells, which can multiply better than they can fully differentiate in vitro, as already discussed (Rusu et al, 2005). In the case of the calf jejunocytes, however, the low level of IAP activity compared to the adult jejunocytes is in agreement with the known immature state of newborn intestinal epithelium (Lebenthal and Lebenthal, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…A likely explanation for this absence of full differentiation could reside in the selection during the primocultures of lowly differentiated stem cells, which can multiply better than they can fully differentiate in vitro, as already discussed (Rusu et al, 2005). In the case of the calf jejunocytes, however, the low level of IAP activity compared to the adult jejunocytes is in agreement with the known immature state of newborn intestinal epithelium (Lebenthal and Lebenthal, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…Immature motility patterns alter normal peristaltic activity and result in overgrowth of anaerobic bacteria in the small intestine with malabsorption of dietary nutrients [23] . In addition, to impaired intestinal motility, premature infants have not yet developed the ability to digest and absorb nutrients and incompletely digested molecules could contribute to intestinal injury [32,33] . Lebenthal and Lee [34] showed that the function of the exocrine pancreas is limited in infants and that pancreatic insufficiency may last through the first year of life.…”
Section: Immature Intestinal Motility Digestion and Barrier Functionmentioning
confidence: 99%
“…Gastrin is responsible for acid secretion and maintenance of the gastric mucosa (Jain and Samuelson, 2006) while CCK promotes digestion through different independent mechanisms (Bragado et al, 1998;Williams, 2001;Thomas et al, 2003). Previous results support the importance of CCK and gastrin for the fetal (Xu and Cranwell, 1991) and neonatal (Lebenthal and Lebenthal, 1999) gastrointestinal development in pigs.…”
Section: Discussionmentioning
confidence: 63%
“…Gastrin is responsible for acid secretion and maintenance of the gastric mucosa (Jain and Samuelson, 2006) while CCK promotes digestion through different independent mechanisms (Bragado et al, 1998;Williams, 2001;Thomas et al, 2003). Previous results support the importance of CCK and gastrin for the fetal (Xu and Cranwell, 1991) and neonatal (Lebenthal and Lebenthal, 1999) gastrointestinal development in pigs.Signaling of chemokine C-X-C motif receptor 4 (CXCR4), a chemokine receptor in the G protein coupled receptor family, was activated as a consequence of maternal supplementation with MRF. Activation of CXCR4 suggests potential regulation of humoral immunity (Nie et al, 2004) since this receptor is expressed commonly by immune cells and, in response to binding its ligand SDF-1 (stromal cell derived factor 1), triggers the migration and recruitment of immune cells (Bleul et al, 1996;Cheng et al, 2000).…”
mentioning
confidence: 91%